Extending local context-based specifications of visual languages. (December 2015) - Costagliola, Gennaro; De Rosa, Mattia; Fuccella, Vittorio
Abstract: In this paper we present a framework for the fast prototyping of visual languages exploiting their local context based specification. In previous research, the local context specification has been used as a weak form of syntactic specification to define when visual sentences are well formed. In this paper we add new features to the local context specification in order to fully specify complex constructs of visual languages such as entity-relationships, use case and class diagrams. One of the advantages of this technique is its simplicity of application and, to show this, we present a tool implementing our framework. Moreover, we describe a user study aimed at evaluating the effectiveness and the user satisfaction when prototyping a visual language.